A mRNA panel for differentiation between acute exacerbation or pneumonia in COPD patients - Bertrams, Wilhelm; Wilhelm, Jochen; Veeger, Pia-Marie; Hanko, Carolina; Brinke, Kristina auf dem; Klabunde, Björn; Pott, Hendrik; Weckler, Barbara; Greulich, Timm; Vogelmeier, Claus F.; Schmeck, Bernd (Frontiers in Medicine, 2024)
Patients suffering from chronic obstructive pulmonary disease (COPD) are prone to acute exacerbations (AECOPD) or community acquired pneumonia (CAP), both posing severe risk of morbidity and mortality. There is no available biomarker that correctly separates AECOPD from COPD. However, because CAP and AECOPD differ in aetiology, treatment and prognosis, their discrimination would be important.This study therefore analysed the ability of selected candidate transcripts from peripheral blood mononuclear cells (PBMCs) to differentiate between patients with AECOPD, COPD & CAP, and CAP without pre-existing COPD.In a previous study, we identified differentially regulated genes between CAP and AECOPD in PBMCs. In the present new cohort, we tested the potential of selected candidate PBMC transcripts to differentiate at early time points AECOPD, CAP+COPD, and CAP without pre-existing COPD. Expression of YWHAG, E2F1 and TDRD9 held predictive power: This gene set predicted diseases markedly better (model accuracy up to 100%) than classical clinical markers like CRP, lymphocyte count and neutrophil count (model accuracy up to 82%).In summary, in our cohort expression levels of YWHAG, E2F1 and TDRD9 differentiated with high accuracy between COPD patients suffering from acute exacerbation or CAP.